2018
DOI: 10.4314/aas.v14i2.11
|View full text |Cite
|
Sign up to set email alerts
|

Management and Outcome of Testicular Torsion

Abstract: Background:Testicular torsion is a common cause of acute scrotum and is complicated by loss of testes. Local data on testicular torsion is limited. This study therefore aimed at determining the incidence and clinical presentation of patients with testicular torsion in our setup.Methods: This retrospective study reviewed files of 90 patients admitted to our hospital with diagnosis of testicular torsion from January 2011 to December 2015.Results: The mean age of presentation was 19± 6 years. Fifty-nine (66%) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Contrary to our findings, multiple studies in high-income countries reported much lower percentages of orchiectomy including: 42% in Iowa [ 13 ], 28% in Canada [ 14 ] and 40% in Jordan [ 15 ]. Studies that reported significantly higher rates of orchiectomy include one in Kenya with 82% [ 4 ], and another in Ethiopia where 83% had orchiectomy [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Contrary to our findings, multiple studies in high-income countries reported much lower percentages of orchiectomy including: 42% in Iowa [ 13 ], 28% in Canada [ 14 ] and 40% in Jordan [ 15 ]. Studies that reported significantly higher rates of orchiectomy include one in Kenya with 82% [ 4 ], and another in Ethiopia where 83% had orchiectomy [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The acutely painful scrotum has been described as a urologic emergency, requiring a high index of clinical suspicion, and prompt surgical intervention with the management aimed at avoiding testicular loss and infertility [ 1 ]. Usually, salvage rates depend on the duration of symptoms and speed of diagnosis [ 4 ]. A study reported that the salvage rate is high if the treatment is initiated within six hours after the onset of symptoms, and inversely decreases with the increase in duration of symptoms [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The acutely painful scrotum has been described as a urologic emergency requiring a high index of clinical suspicion and prompt surgical intervention with the management aimed at avoiding testicular loss and infertility (1). Usually, salvage rates depend on the duration of symptoms and speed of diagnosis (4). A study reported that the salvage rate is high if the treatment is initiated within six hours after the onset of the symptoms and inversely decreases with increase in duration of symptoms (5).…”
Section: Introductionmentioning
confidence: 99%
“…Many patients in resource limited settings present late as they are waiting for the pain to resolve with self-medication. Moreover, clinicians may prescribe antibiotics and analgesics when a misdiagnosis has been made resulting in late presentation (4). Generally in our setting, it's unlikely for a patient to present within six hours due to long travel distances to access surgical specialty services and also the tendency to use alternative medicine.…”
Section: Introductionmentioning
confidence: 99%